The AD8 (Dementia Screening Interview) is a valid and reliable screening scale not only for dementia but also for mild cognitive impairment in the Turkish geriatric outpatients. (20th June 2018) - Usarel, Cansu; Dokuzlar, Ozge; Aydin, Ali Ekrem; Soysal, Pinar; Isik, Ahmet Turan
ABSTRACT: Introduction: There is still a need for short, practical, and daily-appropriate scales to distinguish between normal cognitive aging, mild cognitive impairment (MCI), or dementia for patients with memory complaints. This study aimed to determine validity and reliability of AD8 (Dementia Screening Interview) to detect both MCI and dementia in Turkish geriatric outpatients. Methods: Comprehensive geriatric assessment was performed in 334 patients, who attended with their informants to the geriatric outpatient clinic for memory complaints. In addition to the AD8, they were screened using Clinical Dementia Rating scale (CDR) and Mini-Mental State Examination. The diagnosis of dementia and MCI was made according to the Diagnostic and Statistical Manual of Mental Disorders - fifth edition (DSM-5) criteria. Results: The mean age of the patients was 74.5±8.5. Of them, 156 were considered as non-cognitive impairment, 60 as MCI, and 118 as dementia. Cronbach's α value of the AD8 was 0.928. The total AD8 scores were found to be negatively correlated with the MMSE scores ( r = −0.801), and positively correlated with CDR score ( r = 0.879) ( p < 0.001, for each). The area under the receiver-operating characteristics curve was 0.979 for cognitive impairment, and 0.999 for dementia. We found that AD8 can show dementia and MCI when the cut-off values are ≥5 and 3–4, respectively, with a sensitivity of 100% and 81.67% and specificity of 96.3% and 93.59%. Conclusion: AD8 is one of the fast, simple, and sensitive screening methods for detecting both minor and major cognitive impairments. With regard to these features, it can be used in older adults attending the primary care settings with memory complaints.